Academic Procrastination of High School Students in East Java - Arbin Janu Setiyowati; Triyono Triyono; Indriyana Rachmawati; Nurul Hidayati (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2020)
This study aims to obtain a comprehensive view of academic procrastination carried out by students in terms of cognitive, affective, and behavior. This study used a survey research method. The population of this research is high school students in East Java and the research sample is 200 students spread over Malang, Blitar, Bangkalan, and Lamongan. The sampling technique used cluster random sampling and the data were analyzed using descriptive statistics. The results showed that the cognitive, affective, and psychomotor descriptions of students' academic procrastination were found. Counselors can use the findings of this study as the basis for developing BK services, especially in designing intervention strategies to reduce academic procrastination of high school students.